Event‐related potential and eye tracking evidence of the developmental dynamics of face processing. (12th February 2014) - Meaux, Emilie; Hernandez, Nadia; Carteau‐Martin, Isabelle; Martineau, Joëlle; Barthélémy, Catherine; Bonnet‐Brilhault, Frédérique; Batty, Magali
Abstract Although the wide neural network and specific processes related to faces have been revealed, the process by which face‐processing ability develops remains unclear. An interest in faces appears early in infancy, and developmental findings to date have suggested a long maturation process of the mechanisms involved in face processing. These developmental changes may be supported by the acquisition of more efficient strategies to process faces (theory of expertise) and by the maturation of the face neural network identified in adults. This study aimed to clarify the link between event‐related potential (ERP) development in response to faces and the behavioral changes in the way faces are scanned throughout childhood. Twenty‐six young children (4–10 years of age) were included in two experimental paradigms, the first exploring ERPs during face processing, the second investigating the visual exploration of faces using an eye‐tracking system. The results confirmed significant age‐related changes in visual ERPs (P1, N170 and P2). Moreover, an increased interest in the eye region and an attentional shift from the mouth to the eyes were also revealed. The proportion of early fixations on the eye region was correlated with N170 and P2 characteristics, highlighting a link between the development of ERPs and gaze behavior. We suggest that these overall developmental dynamics may be sustained by a gradual, experience‐dependent specialization in face processing (i.e. acquisition of face expertise), which produces a more automatic and efficient network associated with effortless identification of faces, and allows the emergence of human‐specific social and communication skills.